Blocking Mechanism of Porn Website in India: Claim and Truth - Pandey, Saurabh; Sharma, Harish (International Journal of Computer Sciences and Engineering, 2019)
In last few years, the addiction of internet is apparently recognized as the serious threat to the health of society. This internet addiction gives an impetus to pornographic addiction because most of the pornographic content is accessible through internet. There have been ethical concerns on blocking the contents over internet. In India Uttarakhand High court has taken initiative for the blocking of pornographic content over internet. Technocrats are coming up with various innovative mechanisms to block the content over internet with various techniques. All though long ago in 2015, the Supreme Court of India has already asked to block some of the websites but it could not be materialized. The focus of this research paper is to review the effectiveness of existing web content blocking mechanism of pornographic websites in Indian context.